REGION AND REGIONALIZATION IN THE STATE OF MINAS GERAIS AND THEIR LINKS TO PUBLIC POLICIES - Pereira, Claudinei da Silva [UNESP]; Hespanhol, Antonio Nivaldo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2015)
In the current article, we discuss the productive and social characteristics of the State of Minas Gerais, based on an analysis of the processes that have led to unequal regional development. We characterize the regionalizations created by State institutions, and notably the Superintendence for the Development of the Northeastern Region (Superintendencia de Desenvolvimento do Nordeste / SUDENE) and the Institute for the Development of the Northern and Northeastern Regions of the State of Minas Gerais (Instituto de Desenvolvimento do Norte e Nordeste de Minas / IDENE), which define areas aimed at implementing regional planning at the federal and state levels, respectively. We also highlight the actions of civil society organizations that have reclaimed the elaboration and execution of public policies directed to reaching the populations living in semi-arid areas. We have realized that official public policies have tended to deepen regional inequalities in Minas Gerais by granting easier access to private investments in some regions while marginalizing other regions.
Keywords: Region; State; unequal development; SUDENE; Semi-arid area; Minas Gerais